Assessment of adults with low literacy skills: a review of methods - Chyl, Katarzyna; Dębska, Agnieszka; Pokropek, Artur; Szczerbiński, Marcin; Tanaś, Łukasz Lech; Sitek, Michał (Frontiers in Education, 2024)
The paper reviews the methods for assessing different components of reading skills in adults with reading difficulties, along with functional reading skills. We are particularly interested in the assessment methods available to researchers and practitioners, developed predominantly in the research context, and not available solely in English. We discuss the large-scale international study, PIAAC, as an example of a framework for such assessments. Furthermore, we cover the following types of assessment tools: 1) self-assessment questionnaires, probing into comprehension difficulties and reading habits; 2) measures of print exposure, such as author recognition tests, correlating with other reading-related skills; 3) measures of word recognition and decoding, including reading aloud of words and pseudowords, as well as silent lexical decision tasks; 4) fill-in-the-blank tasks and sentence reading tasks, measuring predominantly local comprehension, entangled with decoding skills; 5) comprehension of longer reading passages and texts, focusing on functional texts. We discuss comprehension types measured by tests, text types, answer formats, and the dependence problem, i.e., reading comprehension tests that can be solved correctly without reading. Finally, we tap into the new ideas emerging from the AI systems evaluation, e.g., using questions generated from news articles or Wikipedia or asked directly by search engines users. In the concluding section, we comment on the significance of incorporating background information, motivation, and self-efficacy into the assessment of adult literacy skills.